Floating tablets of hydralazine hydrochloride: optimization and evaluation - Kondi Vanitha; Mohan Varma; Alluri Ramesh (Universidade de São Paulo, 2013)
Hydralazine hydrochloride has a half-life of 2 to 4 hours with an oral bioavailability of 26-50%. Since hydralazine has a demethylating effect on various suppressor genes, it can be used in various types of cancer to support chemotherapy. The purpose of this study was to optimize and evaluate floating tablets of hydralazine hydrochloride designed to prolong the gastric residence time and to provide controlled release of the drug for 14 h. The floating tablets of hydralazine hydrochloride were prepared by the wet granulation method. Semi-synthetic polymers of hydroxy propyl methyl cellulose (HPMC K100M) and ethyl cellulose were used as the release retarding agents. A 2² factorial design was applied to systematically optimize the drug release profile. The concentrations of HPMC K100M and ethyl cellulose were optimized to provide controlled release of hydralazine for 14h. Non-Fickian diffusion release transport was confirmed as the release mechanism for the optimized formulation and the predicted values agreed well with the experimental values. Drug excipient compatibility studies were investigated by FTIR, DSC and XRD. These data indicate that there were no chemical interactions between the drug and the polymer. In vivo X-ray imaging showed floating tablet performance in rabbits.